1991
DOI: 10.1007/bf00228968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of percutaneous stimulation on motor unit firing behavior in man

Abstract: Summary. Motor unit firing behavior in human first dorsal interosseous (FDI) muscle was studied during controlled constant force isometric contractions. The threshold at which motor-units were recruited and the mean firing rate at SO" of maximal voluntary contrac tion (MVq were evaluated following stimulation of the skin area over the second digit. Stimulation of cutaneous receptors tended to increase the recruitment threshold of most of the motor units recruited under 20% MVC, while high-threshold motor units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Cutaneous input can change motor unit recruitment threshold and firing rate (Masakado et al, 1991). Some studies have reported that skin cooling (SC), which is a kind of the cutaneous input, induced by the cold environment or cold air, with minimal change of muscle temperature, enhances muscle activity (Rissanen et al, 1996, Winkle and Jorgensen, 1991, Yona, 1997.…”
Section: Introductionmentioning
confidence: 98%
“…Cutaneous input can change motor unit recruitment threshold and firing rate (Masakado et al, 1991). Some studies have reported that skin cooling (SC), which is a kind of the cutaneous input, induced by the cold environment or cold air, with minimal change of muscle temperature, enhances muscle activity (Rissanen et al, 1996, Winkle and Jorgensen, 1991, Yona, 1997.…”
Section: Introductionmentioning
confidence: 98%
“…Several other studies have also demonstrated a change in MU recruitment pattern. In some subjects HT-MU activation threshold was reduced, whereas in others, there was a reversal in the MU recruitment pattern when low-threshold (LT)-MUs were inhibited and HT-MUs were facilitated [17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also show decreased discharge rates of low and moderate threshold motor units with pain (40 -42) and a parallel firing rate increase in high threshold units (27). Based on findings of nonuniform effects of pain on motoneuron discharge, it has been argued that pain may selectively inhibit low-threshold units (type I fibers) and at the same time favor recruitment of additional high-threshold units (which may include type II fibers) (41,43). According to the size principle, higher threshold units produce greater force than lower threshold units (44), and these units are more responsive to resistance training than lower threshold units (45).…”
Section: Discussionmentioning
confidence: 99%